Midterm Follow-Up of Familial Hypercholesterolemia from a Cross-Sectional School-Based Cholesterol Screening Program - Rachel Kohler, BS; Christa Lilly, PhD; Page Poffenberger, BA; Will Burton; Naby Damarputra, DDS; Lesley Cottrell, PhD; Eloise Elliott, PhD; Lee A. Pyles, MD (Elsevier, 2024)
Objective: The Coronary Artery Risk Detection in Appalachian Communities (CARDIAC) project surveyed cardiometabolic risk factors to identify risk for adult heart disease through a school-based program. This current investigation determined the follow-up status of children who were identified with elevated low-density lipoprotein cholesterol (LDL-C) level that suggests a diagnosis of familial hypercholesterolemia (FH). We hypothesized deficient follow-up of persons identified with probable FH from screening LDL-C in West Virginia (WV) fifth-grade classes. Other markers suggested ongoing health care for many of these persons. Study design: Between 1998 and 2016, 60 404 children in the fifth grade had LDL-C levels identified through the CARDIAC Project. Of the 632 children who had probable FH, 398 were subsequently identified through the electronic health record, phone calls, and mail surveys. The institutional review board at West Virginia University approved verbal consent for follow-up. Information obtained included any medical care, medications including cholesterol-lowering (CLM), and family history of cardiac events. Results: Of the 398 children previously screened in WV CARDIAC Project, 75 (19%) had follow-up lipid panels. Fifty-six subjects not on a CLM had an LDL-C that was 27.96 ± 93.4 mg/dL lower than the fifth-grade baseline (P < .001), whereas no significant change was seen in those on a CLM. Overall, 46% of participants indicated no health care interaction after screening, and 34% of participants showed interaction without a follow-up lipid panel. Conclusions: A suboptimal midterm effect of FH identification was noted in fifth graders. Universal screening as was offered in WV must be linked to a follow-up system that engages primary providers, parents, and children to embrace life-saving preventive practices.